The effect of pay for performance on risk incidence of hip fracture in type 2 diabetic patients: a nationwide population-based cohort study. Issue 12 (March 2020) - Lee, Yung-Heng; Kung, Pei-Tseng; Kuo, Wei-Yin; Kao, Su-Ling; Tsai, Wen-Chen
Abstract: Objectives: Diabetes mellitus (DM) increases the risk of hip fracture. The literature rarely discusses the importance of pay-for-performance (P4P) programs for the incidence of hip fractures in patients with type 2 DM (T2DM). This study aimed to examine the impact of the P4P program on hip fracture risk in patients with T2DM. Methods: This retrospective cohort study focused on data from T2DM patients aged 45 and older between 2001 and 2012. We continued to track these data until 2013. The data were collected from the National Health Insurance Research Database in Taiwan. To minimize selection bias, T2DM patients were divided into P4P enrollees and non-enrollees. Propensity score matching by greedy matching technique (1:1 ratio) was used to include 252, 266 participants. A Cox proportional hazard model was performed to examine the impact of the P4P program on hip fracture risk. We used the bootstrap method to perform sensitivity analysis by random sampling with replacement. Results: Our results showed that the risk of hip fracture in P4P enrollees was 0.92 times that of non-enrollees. (hazards ratio [HR] = 0.92; 95% confidence interval [CI]: 0.85–0.99). P4P enrollees who received regular treatment had lower risk in the first 4 years (HR = 0.90; 95%CI: 0.84–0.96) but no statistically significant difference after 4-year enrollment (HR = 0.99; 95%CI: 0.93–1.06). There was no statistically significant difference in the effect of hip fractures between P4P non-enrollees and P4P enrollees with irregular treatment (HR = 0.94, 95%CI: 0.87–1.03). Through sensitivity analysis, the results also showed P4P enrollees had a lower risk of hip fracture compared to P4P non-enrollees (mean HR = 0.919; 95% CI: 0.912–0.926). Stratified analysis showed that patients without DM complications (DCSI = 0) who enrolled in P4P had lower risks of hip fractures than the non-enrollees (HR = 0.90; 95% CI: 0.82–0.98). Conclusion: T2DM patients enrolled in P4P program can reduce the risks of hip fracture incidence. Early inclusion of patients without DM complications in the P4P program can effectively reduce hip fractures.